Analysis of Regional Development Income Budget Towards Efficiency and Effectiveness of Development Budget Government Government Sector South Sulawesi - S, Nurhidayanti; Ruslan, Muhlis; Menne, Firman (Indonesian Journal of Business and Management, 2018)
Research location in South Sulawesi Province in 2013-2015. Measurement analysis uses Financial and Value For Money Aspects of efficiency and effectiveness. This study aims to analyze how: (1) the consistency between the Regional Expenditure Revenue Budget and the realization of the education sector development budget management of the South Sulawesi provincial government in terms of financial aspects, (2) the level of efficiency and effectiveness of the allocation of development budget management in the education sector from the Regional Expenditure Budget seen from the realization of the budget, expenditure plans and realization of the education sector expenditure in the South Sulawesi provincial government. The results of this study indicate that: (1) there is consistency between the regional expenditure budget and the realization of the development budget management in the education sector of the government of South Sulawesi Province in terms of financial aspects, (2) governance of the development budget in the education sector allocated from the expenditure budget In terms of budget realization, the expenditure plan and realization of the education sector expenditure in the provincial government of South Sulawesi are said to be efficient with a value of more than 90% and the level of effectiveness by paying attention to the outcome achieved.